Cultures in Translation: Toward Preserving Authentic Expression in Literary Translation (Heritage, 2023)
• Translation has a significant role in intercultural communication and the exact rendering of complex culturally determined meanings of lexical items poses a big challenge for a translator. Since literary works often teem with historical and cultural characteristics of a nation, it is of utter importance to encourage the study of the interrelation between language and culture on the one hand and the nature of translation on the other. This paper reports on the analysis of translation equivalents of lexical items found in translations of excerpts taken from Ivo Andric's novel The Woman from Sarajevo. This paper aims to draw attention to the complex nature of the process of translation, focusing on those lexical items that are culturally specific and demand more attention. It also shows how the authentic expression changes as regards semantics and syntactic properties of a sentence. The analysis of translation equivalents shows that, if we aim at preserving cultural identity, it is necessary to know numerous complex socio-historical and cultural aspects because not only the content is transmitted but the culture of the original language as well.
Keywords: translation, translation equivalent, intercultural communication, authenticity